Performance, carcass and meat quality of pigs submitted to immunocastration and different feeding programs - Dalla Costa, Osmar A.; Tavernari, Fernando de C.; Lopes, Leticia dos S.; Dalla Costa, Filipe A. [UNESP]; Feddern, Vivian; de Lima, Gustavo J.M.M. (Elsevier, 2020)
The feed restriction of pigs aims to improve the nutrient utilization of the diet, reduce carcass fat and increase lean meat. Immunocastration is a painless, reversible technique that improves animal welfare, decreases boar taint in meat, leading to lower fat deposition and increases lean meat. This study aimed at evaluating either feeding (restricted) programs (FP) and castration categories (surgically castrated × immunocastration) in terms of pig performance, carcass traits and meat quality. Castration category and FP did not influence marbling, initial pH and drip loss in loin and ham. However, immunocastrated pigs presented lighter loins and hams with lower ultimate pH, compared to the surgically castrated pigs. The FP with lower feed volume resulted in higher ultimate pH. Immunocastrated males had a higher live weight than those surgically castrated. Also, the more the feed supply decreased, the better the feed conversion. Immunocastrates had lower carcass yields, however these pigs had their backfat thickness decreased and lean meat increased in the carcass, without affecting the loin depth.
Keywords: Ham; Lean meat; Loin; Surgical castration; Welfare; Zootechnical parameters